Evening Expression of Arabidopsis GIGANTEA Is Controlled by Combinatorial Interactions among Evolutionarily Conserved Regulatory Motifs . Issue 10 (31st October 2014) - Berns, Markus C.; Nordström, Karl; Cremer, Frédéric; Tóth, Réka; Hartke, Martin; Simon, Samson; Klasen, Jonas R.; Bürstel, Ingmar; Coupland, George
Abstract : Integration of environmental cues and circadian clock control confers daily rhythms in gene expression. GIGANTEA regulates flowering as well as stress responses, and its transcription peaks in the evening. In this work, evolutionary comparisons, whole-genome data, and dissection of promoters were used to define combinations of motifs that confer evening expression and light induction of GIGANTEA . Abstract: Diurnal patterns of gene transcription are often conferred by complex interactions between circadian clock control and acute responses to environmental cues. Arabidopsis thaliana GIGANTEA ( GI ) contributes to photoperiodic flowering, circadian clock control, and photoreceptor signaling, and its transcription is regulated by the circadian clock and light. We used phylogenetic shadowing to identify three evolutionarily constrained regions (conserved regulatory modules [CRMs ]) within the GI promoter and show that CRM2 is sufficient to confer a similar transcriptional pattern as the full-length promoter. Dissection of CRM2 showed that one subfragment (CRM2-A) contributes light inducibility, while another (CRM2-B) exhibits a diurnal response. Mutational analysis showed that three ABA RESPONSE ELEMENT LIKE (ABREL) motifs in CRM2-A and three EVENING ELEMENTs (EEs) in CRM2-B are essential in combination to confer a high amplitude diurnal pattern of expression. Genome-wide analysis identified characteristic spacing patterns of EEs and 71 A. thaliana promoters containing three EEs. Among these promoters, that of FLAVIN BINDING KELCH REPEAT F-BOX1 was analyzed in detail and shown to harbor a CRM functionally related to GI CRM2. Thus, combinatorial interactions among EEs and ABRELs confer diurnal patterns of transcription via an evolutionarily conserved module present in GI and other evening-expressed genes.